Simulating behavior of petroleum compounds during refinery effluent treatment using the SimpleTreat model. (January 2021) - Thunnissen, Naomi W.; van de Meent, Dik; Struijs, Jaap; Hjort, Markus; Redman, Aaron D.; Smit, Mathijs G.D.; Hendriks, A. Jan; van Zelm, Rosalie
Abstract: Distribution and elimination of petroleum products can be predicted in aerobic wastewater treatment plants (WWTPs) using models such as multimedia fate model SimpleTreat. An advantage of the SimpleTreat model is that it only requires a few basic properties of a chemical in wastewater to calculate partitioning, biodegradation and ultimately emissions to air, surface water and produced sludge. The SimpleTreat model structure reflects a WWTP scheme. However, refinery WWTPs typically incorporate more advanced treatment processes such as dissolved air flotation (DAF), a process that clarifies wastewaters by the removal of suspended matter such as oil or solids. The objective of this work was to develop a WWTP removal model that includes DAF treatment. To understand how including a DAF in the model affects the predicted concentrations of petroleum constituents in effluent, we replaced the primary sedimentation module in SimpleTreat with a module simulating DAF. Subsequently, we compared results from the WWTP-DAF model with results obtained with the original SimpleTreat model for a library of over 1500 representative hydrocarbon constituents. The increased air-water exchange in a WWTP-DAF unit resulted in higher predicted removal of volatile constituents. Predicted removal with DAF was on average 17% larger than removal with primary sedimentation. We compared modelled results with measured removal data from the literature, which supported that this model refinement continues to improve the technical basis of assessment of petroleum products. Highlights: Dissolved air flotation (DAF) was included in multimedia model SimpleTreat. Predicted removal with DAF was on average 17% larger than removal with primary sedimentation. More removal via air was predicted with DAF due to injected gas bubbles. The improved model supports reliable risk assessment of petroleum products.